Acceptability of woman‐delivered HIV self‐testing to the male partner, and additional interventions: a qualitative study of antenatal care participants in Malawi. Issue 1 (26th June 2017) - Choko, Augustine Talumba; Kumwenda, Moses Kelly; Johnson, Cheryl Case; Sakala, Doreen Wongera; Chikalipo, Maria Chifuniro; Fielding, Katherine; Chikovore, Jeremiah; Desmond, Nicola; Corbett, Elizabeth Lucy
Abstract: Introduction : In the era of ambitious HIV targets, novel HIV testing models are required for hard‐to‐reach groups such as men, who remain underserved by existing services. Pregnancy presents a unique opportunity for partners to test for HIV, as many pregnant women will attend antenatal care (ANC). We describe the views of pregnant women and their male partners on HIV self‐test kits that are woman‐delivered, alone or with an additional intervention. Methods : A formative qualitative study to inform the design of a multi‐arm multi‐stage cluster‐randomized trial, comprised of six focus group discussions and 20 in‐depth interviews, was conducted. ANC attendees were purposively sampled on the day of initial clinic visit, while men were recruited after obtaining their contact information from their female partners. Data were analysed using content analysis, and our interpretation is hypothetical as participants were not offered self‐test kits. Results : Providing HIV self‐test kits to pregnant women to deliver to their male partners was highly acceptable to both women and men. Men preferred this approach compared with standard facility‐based testing, as self‐testing fits into their lifestyles which were characterized by extreme day‐to‐day economic pressures, including the need to raise money for food for their household daily. Men and women emphasized the need for careful communication before and after collection of the self‐test kits in order to minimize the potential for intimate partner violence although physical violence was perceived as less likely to occur. Most men stated a preference to first self‐test alone, followed by testing as a couple. Regarding interventions for optimizing linkage following self‐testing, both men and women felt that a fixed financial incentive of approximately USD$2 would increase linkage. However, there were concerns that financial incentives of greater value may lead to multiple pregnancies and lack of child spacing. In this low‐income setting, a lottery incentive was considered overly disappointing for those who receive nothing. Phone call reminders were preferred to short messaging service. Conclusions : Woman‐delivered HIV self‐testing through ANC was acceptable to pregnant women and their male partners. Feedback on additional linkage enablers will be used to alter pre‐planned trial arms.